#TITLE_ALTERNATIVE# - MOCHAMAD TOFAN S. (NIM 12303020), R.
The result of VLF-EM was not satisfied for mapping anomaly that was caused by conductor. However, qualitative interpretation of VLF data can't determine the anomaly depth accurately. In this final project I have used VLF-EM-vGRAD method for getting qualitative interpretation and quantitative interpretation from inversion. These methods was applied to subsurface river in karst region Bribin, Semanu. VLF-EM-vGRAD method was based on the define that delta of magnetic field value in different height was caused only by conductive material in subsurface. Whether the inversion was used to get the subsurface resistivity model. By applied these methods, the flow trend of subsurface river can clearly detected and easy to be investigated. From resistivity inversion model, we can predict the depth of subsurface river, so the flow direction of subsurface river can be predicted. Integrating qualitative and quantitative interpretation region of Depan Kantor Bribin yield the flow subsurface river moved from north to south and didn't accross region of Belakang Kantor Bribin. Pratically, quantitative interpretation need qualitative interpretation for inversion process input, so the result of interpretation is more accurate.